Metabolic interactions: how gut microbial metabolites influence colorectal cancer - Qinhan Cao; Qinhan Cao; Meiju Yang; Min Chen (Frontiers in Microbiology)
Colorectal cancer (CRC) is a growing public health concern due to its rising incidence and high rate of cancer-associated deaths. Emerging evidence suggests that gut microbiota and their metabolites are critically involved in the initiation and advancement of CRC. These metabolites, which originate from the breakdown of nutrients from food and host-related substances through microbial activity in the gut, can profoundly influence tumor formation. In addition to well-studied compounds such as short-chain fatty acids (SCFAs), bile acids (BAs), tryptophan metabolites, and polyamines, this review highlights emerging metabolites—including hydrogen sulfide (H₂S) and formate—that have recently drawn attention for their roles in colorectal carcinogenesis. We also incorporate recent mechanistic insights, such as butyrate-induced ferroptosis and H2S-mediated protein persulfidation, to illustrate how microbial metabolites influence cancer cell metabolism. Moreover, the potential of microbial metabolites as biomarkers for early diagnosis and prognosis of CRC is discussed. Therapeutic strategies targeting microbial metabolites—such as dietary modulation, combination therapies, fecal microbiota transplantation (FMT), and phage therapy—are also reviewed. By providing a comprehensive and up-to-date overview of microbial metabolic networks associated with CRC, this review underscores the critical functions of gut microbial metabolites in tumorigenesis, offering novel insights into their utility as diagnostic and prognostic biomarkers, as well as promising therapeutic targets.